Salmon Calcitonin Exerts an Antidepressant Effect by Activating Amylin Receptors - Jiang, Jian; Ju, Jun; Luo, Liang; Song, Ze; Liao, Huanquan; Yang, Xiuyan; Wei, Shoupeng; Wang, Dilong; Zhu, Wenhui; Chang, Jinlong; Ma, Junzhe; Hu, Hao; et al. (Frontiers in Pharmacology, 2022)
Depressive disorder is defined as a psychiatric disease characterized with the core symptoms of anhedonia and learned helplessness. Currently, the treatment of depression still calls for the medications with high effectiveness, rapid action and few side effects, although many drugs, including fluoxetine and ketamine, have been approved for clinical usage by FDA. In this study, we focused on calcitonin as a polypeptide, of which the antidepressant effect has not been reported, even if calcitonin gene-related peptides have been previously demonstrated to improve depressive-like behaviors in rodents. Here, the antidepressant potential of salmon calcitonin (sCT) was first evaluated in chronic restraint stress (CRS) mouse model of depression. We observed that the immobility duration in CRS mice was significantly increased during the tail suspension test and forced swimming test. Furthermore, a single administration of sCT was found to successfully rescue depressive-like behaviors in CSR mice. Lastly, AC187 as a potent amylin receptor antagonist was applied to investigate the roles of amylin receptors in depression. We found that AC187 significantly eliminated the antidepressant effects of sCT. Taken together, our data revealed that sCT could ameliorate a depressive-like phenotype probably via the amylin signaling pathway. sCT should be considered as a potential therapeutic candidate for depressive disorder in the future.